A new genus and species of Melitidae (Crustacea: Amphipoda: Hadzioidea) from Brazilian waters - Senna, André R.; Serejo, Cristiana S. (Zootaxa, 2012)
A new genus and species of the Eriopisella group are described from Brazilian waters. The new genus is monotypic andclosely related to the melitid genus Netamelita Barnard, 1962, but is distinguishable from the latter by the propodus ofgnathopods 1 and 2 that is wedge-shaped, subtriangular and has the palm longer than posterior margin. This is the first amphipod of the Eriopisella group reported from Brazil.